Plan de marketing turístico territorial que fomente el desarrollo sostenible del cantón Chone - Mera Zambrano, Ángela Valeria (2017)
The present research aimed at designing a territorial tourism marketing plan to promote the sustainable development in Chone city. For this purpose, three phases were structed: the first one, the situational diagnosis was made, in which the study area was characterized and delimited, the SWOT matrix was made bringing out the variety of touristic resources in the city; as well as the investment possibility, positive aspects that help to mitigate bankruptcy such as lack of touristic planning, whereby adaptive strategies were implemented. It analyzed the offer and the pressure, through the application of surveys directed to tourists and service providers to know the point of view of the visitor, bringing out their discontent and interest, by interviews was possible to determine promotion actions, such as the creation of a territorial tourism brand. The second phase includes the elaboration of the territorial marketing plan, which details the presentation of the plan, the potential axes of communication both internal and external, also a study of potential competencies and direct of the city was made with the objective of knowing the reality in which the study object is found. The third phase describes the visual image of the territorial brand, which is composed of representative elements of Chone. Based on this information, the territorial tourism marketing plan is structured, in which the planning, preparation, implementation and consolidation stages of the plan are highlighted.